The effects of public spending composition on firm productivity - Richard Kneller; Florian Misch (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
This paper exploits the unique institutional features of South Africa to estimate the impact of provincial public spending on health, education and transport on firm productivity. Our identification strategy is based on within industry-province differences between firms of the effects of public spending. We show that public spending composition affects firm productivity depending on the capital intensity of firms relative to the province-industry mean. Our data and empirical specification allow us to rule out that these results are affected by econometric problems that are commonly encountered when estimating the effects of fiscal policy and by unobserved industry- or province-specific productivity shocks. In contrast to related existing microeconomic evidence, we take into account the government budget constraint so that our results have clear policy implications.
urn:nbn:de:bsz:180-madoc-332818
Keywords: D24; H32; H72; O12; 330; Public Spending Composition; Productive Public Spending; Firm Productivity